Valuing Recreational Benefits of Perlis State Park, Malaysia Using Travel Cost Method - Mohammad Afandi, Syamsul Herman (2010)
Outdoor recreational experience is one of the services provided in many natural areas. In planning for the development and operation of outdoor recreational opportunities of public land, valuation of the area is mostly done by establishing a recreational demand model curve. Not only does the demand model illustrate the actual recreational behaviour, it also estimates the economic value generated by outdoor recreation. This study is conducted in the state of Perlis. It is a small state with approximately 14% forest cover. Perlis State Park (PSP) was chosen as the study site, because there has been no forest production for the state of Perlis for several years, even though it still has forested areas. This study, on the recreational use of PSP, seeks to determine its economic value as an alternative income for Perlis. In terms of method, the geographical location of PSP provides variations in distance, and thus, a variety of travelling costs, which are necessary for regression analysis. The estimation of the recreational use value for Perlis State Park (PSP) is conducted by applying the Zonal Travel Cost Method (ZTCM) and the Individual Travel Cost Method (ITCM). In the study, the ZTCM used, is a modification of the basic traditional Claw on model. Modifications were made in terms of including the elements of time,alternative locations,perceptions, and demographic variables. Adding relevant variables enriches the explanatory power of the model, especially the variables that will affect visitation rates. Regression analysis found that visit percapita, is influenced by existing alternative recreational locations, the cost of travelling time, length of stay, expenditure at the site, and monthly income. The motive variables do not capture implicit intention, suggesting that visits may be a combination of the listed benefits or other benefits that were not captured by the model. This transformation has improved the statistical properties of the model. The second type of model (ITCM) is an advanced type of travel-cost method. It is considered better, as it uses actual visitations per year as a dependent variable. To counter endogenous stratification problems and truncation, the model is based on a count-data model, and this has also improved the statistical properties. The economic value of PSP, as a recreational area, is estimated at RM5.3 million with the modified ZTCM; and at RM 19.5 million by applying ITCM. The estimates found from the study, confirm that there is a substantial recreational use value for PSP, which suggests that outdoor recreational activities provide benefits to its visitors. Despite the difference in monetary values, in the ZTCM and the ITCM, the calculated values from both models are dependent on visitation rates. Therefore, it is imperative for the management to maintain an optimum visitation rate to PSP. To this effect, not only are the efforts by the managing agency to promote outdoor recreation in PSP justified, but also, extra effort may be required to attract more tourists to the area as this will increase the economic value.